2016
DOI: 10.1007/978-3-319-45390-3_6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing in Industrial Associations and Science and Technology Parks

Abstract: Knowledge management practices are used in collaborative networks promoting innovation in order to share critical knowledge among network members towards improving organizational results. This paper proposes to explore the channels and practices for knowledge sharing in collaborative networks, by means of an exploratory multiple case study carried out in two types of collaborative networks: (i) industrial associations; and (ii) science and technology parks. Empirical evidence has been collected from interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In contrast, from a commercial perspective, Heydebreck et al (2000) suggested that technology-based start-ups are required to seek out global opportunities to launch their innovations in order to break-even from their R&D expenses, which could partly explain why we find in this study that firms consider business networking events primarily as a way to be near customers. Moreover, the socialisation process among organisations on SPs is beneficial for knowledge sharing as emphasized in Inomata et al (2016). Compared to the other firm types, young technology-based firms associate cost benefits considerably less often with business support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, from a commercial perspective, Heydebreck et al (2000) suggested that technology-based start-ups are required to seek out global opportunities to launch their innovations in order to break-even from their R&D expenses, which could partly explain why we find in this study that firms consider business networking events primarily as a way to be near customers. Moreover, the socialisation process among organisations on SPs is beneficial for knowledge sharing as emphasized in Inomata et al (2016). Compared to the other firm types, young technology-based firms associate cost benefits considerably less often with business support.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen 1999;Byosiere et al 2010). Socialisation among actors on SPs enhances tie strength and therefore eases the transfer of valuable tacit knowledge (Inomata et al 2016). Dettwiler et al (2006) inquired start-ups on the importance of geographical proximity benefits, distinguishing nearness to a university, to customers and to firms (both competing and similar types).…”
Section: Knowledge Sharing and Collaborationmentioning
confidence: 99%
“…Specifically, for these smaller and younger firms the networking events and training are of interest as they lack the financial and organisational capacity to do so on their own (Chan and Lau, 2005;Löfsten and Lindelöf, 2005). Networking events enable the interaction between different co-located actors and repeated interactions between these actors is expected to contribute to knowledge sharing (Inomata et al, 2016). SP tenant firms associate both training programs and business networking events with knowledge sharing and collaboration and to be closer to the university and new clients, while networking events also serve the purpose of meeting other firms (Ng et al, 2019b).…”
Section: Sp Facilities and Servicesmentioning
confidence: 99%
“…In the specific case of SMEs, it appears that due to their resource constraints, SMEs are more dependent than large firms on the services, information and contacts generated through IEAs (Gashi, Hashi, & Pugh, 2013). The recent study of Inomata et al (2016) explores the channels and practices for knowledge sharing in Science and Technology Parks, as well as in IEAs. Knowledge sharing is the process when individuals mutually exchange tacit and explicit knowledge, creating new knowledge in collaboration (van den Hooff & De Ridder, 2004).…”
Section: Industrial Enterprises Associations As Institutional Networkmentioning
confidence: 99%